An evaluation of the effectiveness of e-learning in the context of the Corona pandemic in the public schools of the Northern Jordan Ghour - Bakheet, Wafaa Ahmed (Journal of Educational and Psychological Sciences, 2021)
This study was aimed at assessing the effectiveness of e-learning in the context of the Corona pandemic in the public schools of the Northern Jordan Ghour, and used the descriptive analytical curriculum, and the study sample consisted of (184 students, 68 teachers, 58 guardian, 15 educational supervisors and 15 school principals) from the Directorate of Education of the Northern Jordan Ghour. The results of the study revealed that the evaluation of the effectiveness of e-learning in the context of the Corona crisis from the point of view of teachers was (medium) with mathematical average (3.39 out of 5), and the evaluation of the effectiveness of e-learning in the context of the Corona crisis from the point of view of students was (medium) with mathematical average (2.98). Assessing the effectiveness of e-learning in the context of the Corona crisis from the point of view of public-school principals and educational supervisors was (medium) with an average of (3.14) and an assessment of the effectiveness of e-learning in the context of the Corona crisis from the point of view of parents was (high) with a mathematical average (3.51). It also found that there were no statistically significant differences at the level of (α≤0.05) an evaluation study of the effectiveness of e-learning under the Corona pandemic in the Northern Ghour Public Schools due to gender change. The researcher recommended working on establishing the infrastructure for the use of e-learning techniques, and holding training courses for teachers, supervisors, school principals, students and parents on e-learning. Parents need to be aware of the importance of using technology to enrich the learning process to ensure the successful use of e-learning techniques, and the need for preventive and supervisory education, while promoting the values of self-education among learners.